EXISTENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF MILLENNIAL EMPLOYEES IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 USING A QUANTITATIVE APPROACH - Romi, Mochamad Vrans; Waliah, Siti; Hasanuddin, Bakri; Sriharyati, Santy (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
In the context of the Industrial Revolution 4.0, the existence of Organizational Citizenship Behavior (OCB) of millennial employees is becoming increasingly relevant, and understanding of this phenomenon can be broadened by considering two important aspects: servant leadership and work-life balance. Servant leadership, emphasizing service and individual empowerment, motivates millennial employees to play an active role in positively contributing to the organization. The research aims to analyze the influence of servant leadership and work-life balance on organizational citizenship behavior. The sample in this study consisted of 160 millennial employee respondents who worked in the creative industry sector, determined using a convenience sampling approach. Data collection uses a questionnaire instrument, which is then distributed online. Data analysis uses the SPSS application by displaying data processing results through testing research instruments with validity and reliability tests, multiple regression analysis, coefficient of determination, and hypothesis testing. Based on the results of data analysis, it is stated that servant leadership and work-life balance have a positive and significant effect on organizational citizenship behavior. The research implications stated by reviewing it from the perspective of servant leadership and work-life balance significantly impact human resource management practices and organizational development.